Barriers and facilitators of evidence-based practice from the perspective of nurses who working in northwestern psychiatric centers of Iran - Fatemeh Yousefi (Journal of Research in Medical and Dental Science, 2017)
Evidence-based practice is an indicator of the quality of health and treatment care and plays an important role in improving the quality of nursing care. The purpose of the study was to determine the barriers and facilitators of evidence-based practice from the perspective of nurses working in psychiatric centers in the northwest of Iran. This research is a descriptive cross-sectional study with statistical population includes 270 nurses working in northwest psychiatric hospitals of country. Sample size was selected using census method. Data collecting tools consisted of two parts. The first part of the questionnaire included demographic information of nurses and the second part included a standard questionnaire of barriers and facilitators the evidence-based practice. The collected data were analyzed using descriptive and analytical statistics and SPSS software (ver. 21). The mean score of evaluating the barriers and facilities to apply the results of research in the field of practice in in nurses on the Bases of practice knowledge dimension was 41.54 ± 10.85 , which they had a low score .low in. The overall score in dimension of access barriers and review of evidences was 18.86 ± 7.19, which nurses had a medium score. The mean of total score was 9.93 ± 3.23, which nurses had a low score In the dimension of barriers to practice change based on scientific evidences. Also, the mean total score in self-assessment skills dimension was 13.70 ± 4.56, that nurses had a medium to low score. It is necessary to do needed facilities to reduce existing barriers in order to change the methods of care based on scientific evidences, with proper planning and policy making, and create an appropriate context for nurses in providing care with quality considering the essential role of nurses in maintaining care and promoting the health of the patients.